2012
DOI: 10.5581/1516-8484.20120072
|View full text |Cite
|
Sign up to set email alerts
|

Association of HLA antigens and BCR-ABL transcripts in leukemia patients with the Philadelphia chromosome

Abstract: Objective This study aimed to verify the association between human leukocyte antigens and the bcr-abl fusion protein resulting from t(9;22)(q34;q11) in chronic leukemia myeloid and acute lymphoblastic leukemia patients. Methods Forty-seven bcr-abl positive individuals were evaluated. Typing was performed bymicrolymphocytotoxicity and molecular biological methods (human leukocyte antigens Class I and Class II). A control group was obtained from the data of potential bone marrow donors registered in the Brazilia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
4
0
2
Order By: Relevance
“…Further, an in-depth literature analysis revealed that several of these genes play important roles in cancer ( CDCA3 [ 26 ], ECEL1 [ 27 ], EN1 [ 28 ], HLA-DMB [ 29 , 30 ], SPRR2A [ 31 ], TMEM40 [ 32 , 33 , 34 ]) including acute myeloid leukemia ( CDCA3 [ 35 ], HLA-DMB [ 30 ], RPL18A [ 36 ], PF4 [ 37 , 38 ], PRG3 [ 39 ]) and T cell acute lymphoblastic leukemia ( TLX3 [ 40 ]). Moreover, some of these genes have already been reported to play a role in CML ( AURKB [ 41 ], AZU1 [ 42 , 43 ], HLA-B [ 44 ], HLA-DMB [ 30 ], PF4 [ 45 ]). In addition, a subset of these genes has been associated with cancer therapy responses ( AZU1 [ 42 , 43 ], CDCA3 [ 26 ], CEACAM6 [ 46 ], EN1 [ 28 ], PF4 [ 37 , 38 , 45 ]).…”
Section: Resultsmentioning
confidence: 99%
“…Further, an in-depth literature analysis revealed that several of these genes play important roles in cancer ( CDCA3 [ 26 ], ECEL1 [ 27 ], EN1 [ 28 ], HLA-DMB [ 29 , 30 ], SPRR2A [ 31 ], TMEM40 [ 32 , 33 , 34 ]) including acute myeloid leukemia ( CDCA3 [ 35 ], HLA-DMB [ 30 ], RPL18A [ 36 ], PF4 [ 37 , 38 ], PRG3 [ 39 ]) and T cell acute lymphoblastic leukemia ( TLX3 [ 40 ]). Moreover, some of these genes have already been reported to play a role in CML ( AURKB [ 41 ], AZU1 [ 42 , 43 ], HLA-B [ 44 ], HLA-DMB [ 30 ], PF4 [ 45 ]). In addition, a subset of these genes has been associated with cancer therapy responses ( AZU1 [ 42 , 43 ], CDCA3 [ 26 ], CEACAM6 [ 46 ], EN1 [ 28 ], PF4 [ 37 , 38 , 45 ]).…”
Section: Resultsmentioning
confidence: 99%
“…Se hicieron comparaciones de las frecuencias de las fusiones génicas que codifican para el transcripto p210 (b3a2, b2a2 y la coexpresión b3a2/b2a2) con las informadas en la literatura en trabajos similares. En el análisis de los resultados, de las ocho poblaciones informadas solo tres fueron estadísticamente significativas (13)(14)(15)(16)(17). Para el transcripto b3a2 fueron significativas las diferencias con las poblaciones europea, paquistaní y cubana (10,12,15) en relación a la estudiada en este trabajo, y para el transcripto b2a2 no se hallaron diferencias significativas (tabla 2).…”
Section: Frecuencias De Los Transcriptos De Fusión Bcr-abl Y Sus Fusi...unclassified
“…In this perspective,even if it is well known that different populations show different HLA haplotype frequencies, the findings of Carvalho et al (4) , trying to unravel the issue of the association of HLA molecules with BCR-ABL peptides inside the Brazilian population, have the major advantage of raising novel interests about the immune pathogenesisof CML and the CML immune-mediated therapies. In fact, the Carvalho et al report indicates that BCR-ABL peptides may be presented by different HLA molecules, which inside the specific CML population may elicit a productive (negative association) or ineffective (positive association) binding to leukemic proteins, in comparison with the healthy population.…”
mentioning
confidence: 99%
“…Other scientific studies report analyses of the association between particular HLA alleles and different types of BCR-ABL fusion proteins at a population level, assuming that a negative association of a particular BCR-ABL product with specific HLA alleles suggests that these alleles play a critical role in presenting peptides derived from the chimeric proteins and in eliciting a successful T lymphocyte cytotoxic response ( 3 ) . In this perspective,even if it is well known that different populations show different HLA haplotype frequencies, the findings of Carvalho et al ( 4 ) , trying to unravel the issue of the association of HLA molecules with BCR-ABL peptides inside the Brazilian population, have the major advantage of raising novel interests about the immune pathogenesisof CML and the CML immune-mediated therapies. In fact, the Carvalho et al report indicates that BCR-ABL peptides may be presented by different HLA molecules, which inside the specific CML population may elicit a productive (negative association) or ineffective (positive association) binding to leukemic proteins, in comparison with the healthy population.…”
mentioning
confidence: 99%
See 1 more Smart Citation